Question worth 20 million lives: Why federal housing assistance has not had its Obamacare. (29th July 2020) - Bendaoud, Maroine; Marmor, Theodore R.
Abstract: The equitable character of a policy determines its progressiveness, yet some domestic policies are more equitable than others. The question of how and why this is the case is addressed by studying federal housing and health policies in the United States, a critical case known for its rampant inequalities in both sectors. Although social equity is a fundamental aspect of welfare provision, explaining differences in coverage and government support among policy areas remains a weakness in the literature. This comparative historical analysis shows that both housing assistance and health care suffered from inequities almost as early as their inception. But a progressive reform took shape with the Affordable Care Act (ACA) and extended coverage to 20 million people formerly uninsured. This essay tackles an unsolved puzzle: Why has such grand policy reform never taken place in housing where more than 20 million people are eligible for assistance but do not receive help? We found that it is largely explained by housing assistance distinctiveness with regard to its weak constituency, racial connotation and low public concern. We conclude with the analytical payoffs of studying social equity, both for political scientists and observers of social affairs.